The World Bank’s Country Policy and Institutional Assessment — An Evaluation - World Bank (Washington, DC, 2012)
The World Bank's Country Policy and Institutional Assessment (CPIA) assess the conduciveness of a country's policy and institutional framework to poverty reduction, sustainable growth, and the effective use of development assistance. It plays an important role in the country performance ratings that have been used for allocating resources from the International Development Association (IDA) to eligible countries since 1980. This evaluation takes the premise that beyond informing IDA allocation, the CPIA is useful as a broad indicator of development effectiveness. It assesses the relevance of the content of the CPIA through a review of the economics literature. It also assesses the reliability of CPIA ratings in two ways-through comparing CPIA ratings with similar indicators, and through reviewing the CPIA ratings generation process. Based on these assessments, the evaluation derives recommendations for enhancing the CPIA.